Effects of non-medicated and medicated urea molasses multinutrient blocks on dry matter intake, growth performance,body condition score and feed conversion ratio of saanen lactating does fed conventional diets - Panadi, Mira; Mohamed, Wan Zahari; Rusli, Nor Dini; Mat, Khairiyah (Universiti Putra Malaysia Press, 2018)
In this study, 24 Saanen lactating does raised by a smallholder in Kemahang, Tanah Merah, Kelantan were randomly assigned to four groups with six goats in each group. The trial included evaluation of four dietary treatments, that is, T1: control group fed on basal diet only, which consisted of 3 kg Napier grass (Pennisetum purpureum) and 1 kg commercial goat pellet. Animals in T2, T3 and T4 received equal amounts of basal diet with supplementation of urea molasses multi-nutrient block (UMMB), medicated urea molasses multi-nutrient block (MUMB) and commercial mineral block (CMB) respectively. The total dry matter intake (DMI) (kg/d) in T2 (1.28) and T3 (1.24) were significantly higher (p<0.05) than in T1 (1.14) and T4 (1.15). However, there were no significant differences (p>0.05) between treatments on average daily gain (ADG) and body measurements. Highest ADG (g/d) were recorded in T2 (53.57) followed by T3 (45.63), T4 (39.68) and T1 (37.70). Similar trend was also recorded in body condition score (BCS) but there were no significant differences (p>0.05) between treatments. At the end of the 90 days of feeding trial, both T2 and T3 showed acceptable BCS, that is, at 3.25 and 3.08 respectively, while low BCS were recorded in T1 (2.63) and T4 (2.71). There was significant difference (p<0.05) between treatments on feed conversion ratio (FCR) which were at 0.84, 0.95, 1.20 and 1.46 for T2, T3, T4 and T1 respectively. Both UMMB and MUMB were effective in enhancing appetite, DMI and ADG of the dairy goats, apart from minimising weight loss during lactation.